Students’ Intention to Pursue A Career in Taxation from the Perspective of the Theory of Planned Behavior - Gloria, Gloria; Pontoh, Grace; Amiruddin, Amiruddin (Faculty of Economics dan Business, Atma Jaya Makassar University, 2024)
This research aims to examine and analyze the intention of students to pursue a career in taxation among accounting students at Hasanuddin University. This study uses three constructs in the theory of planned behavior (TPB), namely attitude, subjective norm, and perceived behavioral control, as well as learning experience as a moderating variable. This research uses primary data from questionnaires distributed to 185 respondents, accounting students class 2021-2022. The research results indicate that attitude, subjective norms, and perceived behavioral control influence students' intention to pursue a career in taxation, while learning experience fails to moderate the influence of attitude, subjective norms, and perceived behavioral control on students' intention to pursue a career in taxation.